(untitled) (Northern International Medical College Journal, 2015)
Epilepsy is a complex disorder affecting brain function having a variety of contributing factors. The genetic predisposition plays a key role in the genesis of epilepsy. Antiepileptic drugs (AEDs) provide effective control in majority of patients with different seizure types. But some refractory cases and those who cannot tolerate the conventional AEDs, it is difficult to control the seizures adequately. On the basis of different mechanisms of action and considering the side effects of drugs, various newer approaches have been evolved during the recent years in the rational management of epilepsy. A brief account of these newer treatment modalities has been focused and incorporated in this review in order to enlighten the readers with the possible beneficial effect of this regimen and their limitations as well. Northern International Medical College Journal Vol.5(2) 2014: 353-356